Red war eaudiobook - Flynn, Vince (Mitch Rapp, 2018)
This instant #1 New York Times bestseller and "modern techno-thriller" ( New York Journal of Books ) follows covert operative Mitch Rapp in a terrifying race to stop Russia's gravely ill leader from starting a full-scale war with NATO. When Russian president Maxim Krupin discovers that he has inoperable brain cancer, he's determined to cling to power. His first task is to kill or imprison any countrymen threatening him. But when his illness becomes increasingly serious, he decides on a dramatic diversion—war with the West. Upon learning of Krupin's condition, CIA director Irene Kennedy understands that the US is facing an opponent who has nothing to lose. The only way to avoid a confrontation that could leave millions dead is to send Mitch Rapp to Russia under impossibly dangerous orders. With the Kremlin's entire security apparatus hunting him, he must find and kill a man many have deemed the most powerful in the world. The fate of the free world hangs in the balance in this "timely, explosive novel that shows yet again why Mitch Rapp is the best hero the thriller genre has to offer" ( The Real Book Spy ).